Internalisasi Nilai-Nilai Karakter Kewirausahaan Dalam Pembelajaran Keterampilan Tata Boga Di SMALB Tunarungu (Studi Fenomenologi di SLB Negeri Kota Bandung dan Cimahi) - Saefulah, Aep; Sauri, Sofyan; Malihah, Elly (Jurnal Paedagogy, 2023)
This study aims to reveal phenomena about the process of internalizing entrepreneurial character values in learning culinary skills at SMALB deaf. This research method used a descriptive phenomenological design with a qualitative approach, where the researcher was also a planner who set the focus, selected participants, or informants, as the executor of data collection, interprets data, and draws conclusions. The data was collected using interviews, observation, documentation, and Focus Group Discussion (FGD) techniques. The subjects of this study were teachers and principals at SLB Negeri Kota Bandung and Cimahi. The results of this study showed that the internalization of entrepreneurial character values applied in learning culinary skills was based on teacher choices and agreements and educational unit conditions and was outlined in lesson plans, learning implementation, and learning evaluation. The character values developed by the school were based on the character education strengthening program (PPK), which carries 18-character values, including religious, honesty, tolerant, discipline, hardworking, creativity, independence, democratic, curiosity, national spirit, love of the country, respect for achievements, communicative, love of peace, love of reading, care for the environment, care for social, and be responsible.